Pomsta - Kojnok, Arnold (Slovakia, 2010)
The film is a fictional story about Milan Farkas a resident of one of the Slovak towns - raising a son alone, who after 24 years of work in a glass factory must find another way to support the family. It portraits the economic and economic crisis that has affected today's Slovakia. In the background - a hidden family story. Under no circumstances can the boy learn that his mother is involved in prostitution.
Verzio Film Festival Submission
Keywords: Documentary films